Metabolic characteristics of normal weight central obesity phenotype polycystic ovary syndrome women: a large-scale national epidemiological survey. Issue 4 (October 2018) - Mu, Liangshan; Zhao, Yue; Li, Rong; Lai, Yuchen; Qiao, Jie
Key message: Polycystic ovary syndrome in women with normal weight but central obesity presents a greater risk of insulin resistance and dyslipidaemia compared with those with normal weight and non-central obesity. Abstract: Research question: The aim was to investigate the metabolic profiles of women with normal weight but central obesity in polycystic ovary syndrome (PCOS). Design: In total, 727 women with PCOS from a large-scale epidemiological survey were included. Diagnosis of PCOS was based on Rotterdam criteria. Subjects were categorized into four subgroups: (i) normal weight non-central obesity (NWNCO): body mass index (BMI) ≤18.5 kg/m 2 to <25 kg/m 2 and waist-to-hip ratio (WHR) <0.85; (ii) normal weight central obesity (NWCO): BMI ≤18.5 kg/m 2 to <25 kg/m 2 and WHR ≥0.85; (iii) obese non-central obesity (ONCO): BMI ≥25 kg/m 2 and WHR <0.85; and (iv) obese central obesity (OCO): BMI ≥25 kg/m 2 and WHR ≥0.85. BMI, WHR, blood pressure, glucose and lipid profiles were measured. Results: NWCO subjects had significantly higher percentages of insulin resistance, high triglycerides and low high-density lipoprotein cholesterol (HDL-C) than NWNCO subjects (all P < 0.05), and similar percentages compared with ONCO subjects. Compared with the NWNCO group, the NWCO group had higher age-adjusted risks of insulin resistance, high triglycerides and low HDL-C (odds ratio [OR] = 3.83, 95% confidence interval [CI] = 2.23–6.58; OR = 1.66, 95% CI = 1.00–2.77, OR = 1.60, 95% CI = 1.11–2.30, respectively). Conclusions: PCOS women with normal weight but central obesity had increased risks of insulin resistance and dyslipidaemia compared with normal weight PCOS women without central obesity, suggesting that combining BMI with measurement of central obesity may provide better adiposity-related metabolic risk factor stratification in clinical practice than either method alone.